Statistics for mining engineering - Czaplicki, Jacek M. (CRC Press/Balkema, 2014)
Knowledge about modern statistics is necessary for mining engineers; not only on how statistical analysis of data should be conducted and statistical synthesis should be done, but also on understanding the results obtained and how to use them to make appropriate decisions connected with a mining operation. This book on statistical analysis and synthesis is preceded by a short repetition of the probability theory. A special section about statistical prediction is also included. The text is illustrated by many examples taken from mine practice, moreover the tables required to conduct statistical inference are attached.